The effect of educational computer games on the academic resilience, academic self-regulation, and academic achievement of EFL students - Deng, Lin; Daverpanah, Nikoo; Izadpanah, Siros (Frontiers in Psychology, 2023)
In recent years there has been an increasing interest in educational computer games. The aim of this research was to study academic resilience, academic self-regulation, and academic achievement. The instruments of academic resilience of Samuels (2004), academic self-regulation by Bofard et al. (1995), and academic achievement questionnaire by Pham and Taylors (1994) were used. Few studies have been conducted to investigate these variables. The statistical population of this study includes 665 female students studying in third-grade high school in 2021. Inclusion criteria were female gender, studying in third grade of high school, high school without tuition fees, and willingness to participate in the study. Eligible participants were selected using the multi-stage sampling method. Level 1: The eligible high schools were considered as a cluster. Level 2: Two high schools were selected randomly and assigned to experimental and control groups. Level 3: Each selected high school (experimental /control groups) had two classes in third grade. Out of these, one class was randomly selected in each group. The number of students in each class was 37 students, as a result, total sample size was 74 students. One of the classes (control group) was traditionally educated, and the other one through the researchers-made educational computer game for one semester. After completing the education, the research instruments were performed. Based on the results achieved from the research questions it can be said that the use of education computers has been effective in increasing the academic resilience, academic self-regulation, and academic achievement of the students. It has significant implications for teachers and learners in the EFL context and opens interesting opportunities for administrators and curriculum developers to explore when planning EFL courses.